Determinants Dividen Payout Ratio and Its Impact on Decitions Investment: A cas study on a mining company listed in Indonesia Stock Exchange - Maria Ulfa; Mohammad Noor Salim (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – This study aims to analyze the effect of financial performance on investment decisions with dividend policies (DPR) as intervening variables in mining sector companies listed on the Indonesia Stock Exchange for 2017 to 2020. The independent variables used in this study are financial performance. The financial performance used in this study is Return on Asset (ROA), Current Ratio (CR), Debt to Equity Ratio (DER), Free Cash Flow (FCF), and Dividend Policy (DPR), while the dependent variable is investment decision ( IOS). This study aims to analyze the effect of financial performance on investment decisions with dividend policies (DPR) as intervening variables in mining sector companies listed on the Indonesia Stock Exchange for 2017 to 2020. The independent variables used in this study are financial performance. The financial performance used in this study is Return on Asset (ROA), Current Ratio (CR), Debt to Equity Ratio (DER), Free Cash Flow (FCF), and Dividend Policy (DPR), while the dependent variable is investment decision ( IOS). Methodology/approach – The sample in this study consisted of 13 mining sector companies listed on the Indonesia Stock Exchange (IDX) in the 2017 to 2020 period which was selected based on certain criteria using the purposive sampling method. Analysis of the data used in this study is a multiple Liniear regression analysis (T test and F test) which is processed using Eviews 11.0. Findings – It was found that . the multiple regression models used in this study, the results of partial testing (T test) showed that only two variables namely ROA, and DER with probability of 0.0006 and the most dominant tstatistics were 3,694806 and inflation rates that had a significant effect on investment decisions. In addition, simultaneously (F test) shows that ROA, CR, DER, FCF, jointly affects investment decisions. Novelty/value – Since dividend policy affects investment decisions, it is very important to know the factors that influence dividend policy. Keywords Employee Dividen Payout Ratio, Investment, Dividen Policy